Захист освітніх електронних інформаційних ресурсів - Савенко, С. О. (ХНУРЕ, 2025)
The work examines electronic information resources (EIR) intended for use in the educational process. The specified types and advantages of educational EIRs, requirements and recommendations for their use. The main threats to educational EIRs and areas of protection are formulated: organizational, technical, legal. The essence of EIR determines the specificity of their protection.
Keywords: освітні ресурси; електронний інформаційний ресурс